2005
DOI: 10.1024/0301-1526.34.1.41
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative morbidity and mortality of carotid artery surgery under loco-regional anaesthesia

Abstract: Morbidity and mortality of carotid endarterectomy in loco-regional anaesthesia is comparable to recently published single-centre results. Patients with severe COPD, usually unsuitable candidates for general anaesthesia, can also be treated safely.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 17 publications
0
9
0
1
Order By: Relevance
“…16 The comparison of a fixed dose of UFH compared with a body weight-adjusted dose of LMWH may be a limitation of this study. One aim of this pilot trial, however, was to find an anticoagulant regimen that would overcome the somewhat improvable (although widely used) UFH protocol, which does not consider individual differences of heparin response of patients independent of adjusting for body weight.…”
Section: Discussionmentioning
confidence: 98%
“…16 The comparison of a fixed dose of UFH compared with a body weight-adjusted dose of LMWH may be a limitation of this study. One aim of this pilot trial, however, was to find an anticoagulant regimen that would overcome the somewhat improvable (although widely used) UFH protocol, which does not consider individual differences of heparin response of patients independent of adjusting for body weight.…”
Section: Discussionmentioning
confidence: 98%
“…The similarity continues, with MI being more frequent in the LA procedures. 7,15,[17][18][19]21,[26][27][28]30 The combined analysis of the LA and GA groups reveals a 30-day incidence of major (disabling or fatal) stroke of 1.8% and 30-day combined major stroke and death incidence of 2.8%. These results compare favorably with those of the previous major case series and demonstrate that the operative outcomes of CEA at this center fall within expected targets.…”
Section: Discussionmentioning
confidence: 99%
“…Chiesa et al 18 administered locoregional anesthesia in 96% of 5425 CEA operations and reported the prevalence of perioperative mortality as 0.37% and neurological morbidity as 1.31%. Assadian et al 19 reported a 30-day mortality rate of 0.2% and stroke rate of 2.2% in 1355 CEA operations that were performed with locoregional anesthesia. Halm et al 20 reported that LA might reduce the risk of death and stroke in their study.…”
Section: Discussionmentioning
confidence: 99%
“…The reported prevalence of long-term restenosis ranges from 1% to 36%. 19 These differences in prevalence may be due to variations in design of the studies, duration of follow-up periods, criteria used to define restenosis, or methods of arterial closure. The prevalence rates that were reported in major studies published during the last 10 years are presented in Table 3 .…”
Section: Discussionmentioning
confidence: 99%